Coffee table book: the historical of Masjid Kampung Hulu Melaka / Norrazin Nor Rashid - Nor Rashid, Norrazin (2017)
The development of mosques in Melaka has been around since the beginning of the 14th century again before Melaka officially opened in 1403M. Expansion of the mosque is seen to occur in tandem with the expansion of Islam in Melaka as a function of the mosque that serves as the center of the spread of Islam. As soon as the official Melaka as a Muslim nation, the ruler had to erect a mosque near the Palace to enable people to meet with the King at the time of prayers. The mosque is located on a hill in the southern part of the city state of Melaka near the sultan's Palace and is official at the time of the mosque. Most of those who settled in the area near the mosque consists of high class.